SPIRITUALITAS DIGITAL J. SAGE ELWELL: MENEMUKAN ALLAH DI RUANG DIGITAL BAGI GENERASI Z - Cong, Jhoni; Hasibuan, Serepina Yoshika (The Way: Jurnal Teologi dan Kependidikan, 2025)
Technological disruption has drastically transformed many aspects of life, including the way Generation Z engages with and expresses their spiritual practices in the digital age. Therefore, this article seeks to provide insight into how to build digital spirituality for generation Z who are saturated with digital technology. By using qualitative methods through the digital communication theology approach promoted by J. Sage Elwell, researchers found the inevitability of digital space as a sacred medium where generation Z can meet God personally. This study concludes that digital space is a bridge between God and generation Z, mediating spiritual experiences and providing broad accessibility in developing the faith community of generation Z. Thus, finding God in digital space is something important to strive for so that the spirituality of generation Z can continue to grow.